(untitled) (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2017)
We investigate the Bremsstrahlung originating from fast non-relativistic electron scattering on an atom in the spectral region near the Fano resonance including the polarization channel and interference term. It is shown that the account for polarization Bremsstrahlung leads to a significant increase of the total Bremstrahlung cross section near the Fano resonances. Numerical calculations are carried out for the first autoionization states 2l2l’ of the Helium atom in the framework of the Born approximation that goes beyond the dipole approximation of the dynamic polarizability of the atom.